Estudo da biomecânica ocular e tomografia da córnea em pacientes com ceratocone, forma frustra de ceratocone e em pacientes normais - Souza, Allan Cezar da Luz [UNIFESP] (2016)
Objective: To study ocular biomechanics and corneal tomography in patients with keratoconus, a frustrated form of keratoconus and in normal patients, in order to evaluate whether the parameters derived from the shape of the curve generated by the Ocular Response Analyzer signal could differentiate these groups. Also, evaluate if the combination of the two technologies studied could increase the accuracy in differentiating the groups. Methods: Observational clinical study, type series of comparative cases. We studied 205 eyes of 205 patients considered normal and 177 eyes of 177 patients with keratoconus. In another sample, 78 eyes from 78 patients considered normal and 21 eyes from 21 patients with frustrated form of keratoconus were also studied; Both samples were from patients of the Renato Ambrósio Eyes Institute, Rio de Janeiro, Brazil. In the first sample, corneal hysteresis (HC) and corneal resistance factor (CRF) were compared in two different ways in normal and keratoconus patients. One way to measure the result was the average of two consecutive exams and another form was the single measurement of better quality. Also in the first sample, 37 parameters derived from the shape of the curve generated by the ORA signal were studied. In the second sample, in addition to the aforementioned parameters, 16 tomographic parameters and 15 parameters derived from the ORA curve related to corneal pressure, corneal response time to air murmur and intensity of corneal aplanation (personalized variables) were studied. Results: The results obtained in the first sample demonstrate that biomechanical measurements obtained with the best quality values ??may be more accurate to discriminate eyes with keratoconus from normal eyes than the average of two consecutive measurements. Still in the first sample, the parameters related to the area under the curve peak (p1area and p2area) obtained the best results to discriminate eyes with keratoconus from normal eyes. The results of these parameters were statistically superior to those of HC and FCR. In the second sample, twenty-one parameters presented statistically significant differences between the control group and the frustrating group of keratoconus. Among the parameters derived from the shape of the ORA curve, the best was that related to the area below the first peak (p1area1). Among the personalized variables, the best parameter was that related to the pressure-strain relationship throughout the response cycle (HLA). Among the tomographic parameters, the so-called BAD-D presented the best results. However, the best performance to discriminate normal eyes from the frustrated form of keratoconus was achieved by a parameter derived from a linear model function that combined the best tomographic and biomechanical parameters, surpassing any individual parameter. Conclusion: Biomechanical parameters have the ability to discriminate normal eyes from keratoconus and frustrated eyes of keratoconus. However, due to the large intersection of values, it was not possible to determine cutoff values ??with adequate sensitivity and specificity. The combination of tomographic data and biomechanical parameters can increase our ability to perform such discrimination.